WRKY transcription factors (TFs): Molecular switches to regulate drought, temperature, and salinity stresses in plants - Khoso, Muneer Ahmed; Hussain, Amjad; Ritonga, Faujiah Nurhasanah; Ali, Qurban; Channa, Muhammed Malook; Alshegaihi, Rana M.; Meng, Qinglin; Ali, Musrat; Zaman, Wajid; Brohi, Rahim Dad; Liu, Fen; Manghwar, Hakim (Frontiers in Plant Science, 2022)
The WRKY transcription factor (TF) belongs to one of the major plant protein superfamilies. The WRKY TF gene family plays an important role in the regulation of transcriptional reprogramming associated with plant stress responses. Change in the expression patterns of WRKY genes or the modifications in their action; participate in the elaboration of numerous signaling pathways and regulatory networks. WRKY proteins contribute to plant growth, for example, gamete formation, seed germination, post-germination growth, stem elongation, root hair growth, leaf senescence, flowering time, and plant height. Moreover, they play a key role in many types of environmental signals, including drought, temperature, salinity, cold, and biotic stresses. This review summarizes the current progress made in unraveling the functions of numerous WRKY TFs under drought, salinity, temperature, and cold stresses as well as their role in plant growth and development.